Burden of HIV Infection in Children with Severe Acute Malnutrition at the University of Abuja Teaching Hospital Gwagwalada, Nigeria - Adaora A Okechukwu; Orji A Okechukwu; Ijeoma O Chiaha (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2015)
Background: Human Immunodeficiency Virus (HIV) pandemic has adversely affected the nutritional status of many children in the sub region, an area where malnutrition is also endemic.The study was aimed at assessing the burden of HIV infection among under five with severe acute malnutrition, determine its common forms, the outcomes and associated co-morbidities. Method: A three year prospective study (April 2011 to March 2014) of children aged 6 weeks to 5 years with diagnosis of severe acute malnutrition was carried out in our health institution for the above objectives. Data analysis was conducted using SPSS version 16.0 software and statistical significance set at p < 0.05. Result: Of the 286 severely malnourished children studied, 142(49.2%) males, and 144 (50.3%) females, HIV sero-prevalence was 199 (69.6%, 95% CI = 63.5-76.3%)and highest in the first year of life 85(42.7%). Though uptake of provider-initiated HIV testing and counseling was 100%,95.3% of positive children came in WHO stage 3 and 4 diseases. Persistent diarrhoea 58(29.1%),bronchopneumonia 53(26.6%), septicaemia 49(24.6%), pulmonary tuberculosis 39(19.6%), and oral candidiasis 35(17.6) were the common associated co-morbidities, with vesico-vaginal fistula 4 (2) being the least co-infection.Marasmus 161 (80.9%) was the major form of severe acute malnutrition in positive children, mortality was significantly higher in positive than in negative children (22.6.4%vs. 9.2%; P<0.001), however no difference was seen in those that left against medical advice (13.6% versus 11.5, p value <0.724 among the two groups. Conclusion: Human Immunodeficiency Virus burden was high in children with severe acute malnutrition in our environment, mortality and those that were left against medical advice was also high. Marasmus was the commonest form of severe malnutrition in positive children, and provider initiated counseling should be offered to children at all service delivery points in the hospital and other levels of health services for early detection of HIV infection. Some co-morbidity even when rare could be useful indication for further evaluation for HIV.